2008
DOI: 10.1002/cmdc.200800022
|View full text |Cite
|
Sign up to set email alerts
|

Inhibitors of Inducible NO Synthase Expression: Total Synthesis of (S)‐Curvularin and Its Ring Homologues

Abstract: (S)-Curvularin and its 13-, 14-, and 16-membered lactone homologues were synthesized through a uniform strategy in which a Kochi oxidative decarboxylation and ring-closing metathesis reactions constitute the key processes. In the evaluation of the anti-inflammatory effects of the synthesized compounds in assays using cells stably transfected with a human iNOS promoter-luciferase reporter gene construct, the 14- and 16-membered homologues showed a slightly higher inhibitory effect towards iNOS promoter activity… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
38
1
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 40 publications
(42 citation statements)
references
References 59 publications
2
38
1
1
Order By: Relevance
“…(1)(2)(3)(4)(5)(6). Curvularins inhibit the expression of the inducible nitric oxide synthase (iNOS), thereby acting as anti-inflammatory agents and immune system modulators (7,8). Importantly, 10,11-dehydrocurvularin ( Fig.…”
mentioning
confidence: 99%
“…(1)(2)(3)(4)(5)(6). Curvularins inhibit the expression of the inducible nitric oxide synthase (iNOS), thereby acting as anti-inflammatory agents and immune system modulators (7,8). Importantly, 10,11-dehydrocurvularin ( Fig.…”
mentioning
confidence: 99%
“…We have recently shown that the assembly of 10,11-dehydrocurvularin (2), a phytotoxic dihydroxyphenylacetic acid lactone (DAL) from Aspergillus terreus, uses a similar chemical modularity principle (20). Curvularins modulate the mammalian immune system by repressing the inducible nitric oxide synthase (21,22). In addition, both monocillin II (1) and 10,11-dehydrocurvularin (2) act as promising broad spectrum inhibitors of various cancer cell lines in vitro by overwhelming the heat shock response, an evolutionarily conserved coping mechanism of eukaryotic cells that maintains protein homeostasis (23)(24)(25)(26).…”
mentioning
confidence: 99%
“…Our previous analyses showed that SC inhibits the JAK/STAT pathway (STAT-1␣-phosphorylation) and thereby proinflammatory gene expression in different human and murine cell systems (Yao et al, 2003;Elzner et al, 2008;Schmidt et al, 2010; and data not shown). In addition, SC was able to reduce proinflammatory gene expression in LPS-treated mice in vivo (data not shown).…”
Section: Resultsmentioning
confidence: 89%